2013
DOI: 10.1002/ggge.20180
|View full text |Cite
|
Sign up to set email alerts
|

Early‐stage rifting of the northern Tyrrhenian Sea Basin: Results from a combined wide‐angle and multichannel seismic study

Abstract: [1] Extension of the continental lithosphere leads to the formation of rift basins and ultimately may create passive continental margins. The mechanisms that operate during the early stage of crustal extension are still intensely debated. We present the results from coincident multichannel seismic and wide-angle seismic profiles that transect across the northern Tyrrhenian Sea Basin. The profiles cross the Corsica Basin (France) to the Latium Margin (Italy) where the early-rift stage of the basin is well prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 57 publications
6
58
0
Order By: Relevance
“…The WAS data do not constrain well crustal thickness beneath the island, but complementary gravity modeling indicates a ≤24 km thickness, in agreement with previous seismic estimations [ Di Stefano et al ., ]. Other WAS profiles acquired during the MEDOC‐2010 experiment in the Northern Tyrrhenian basin, across Corsica and offshore to the east, suggests a similar thickness beneath the island [ Moeller et al ., ]. The crystalline crust thins from ~15 km thick under the coastline (80 km, Figure a) to 9 km at domain 1 edge, implying a stretching factor ( ß ) of ~3 (125 km, Figure a).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The WAS data do not constrain well crustal thickness beneath the island, but complementary gravity modeling indicates a ≤24 km thickness, in agreement with previous seismic estimations [ Di Stefano et al ., ]. Other WAS profiles acquired during the MEDOC‐2010 experiment in the Northern Tyrrhenian basin, across Corsica and offshore to the east, suggests a similar thickness beneath the island [ Moeller et al ., ]. The crystalline crust thins from ~15 km thick under the coastline (80 km, Figure a) to 9 km at domain 1 edge, implying a stretching factor ( ß ) of ~3 (125 km, Figure a).…”
Section: Discussionmentioning
confidence: 98%
“…From a morphotectonic point of view, the Tyrrhenian Sea can be subdivided in three different domains (Figure ); the Northern (north of ~40° 45′N), which displays shallower seafloor and rough morphology; the Central (from ~40° 45′N to ~39°N) with deeper seafloor and extended abyssal plains spotted with prominent volcanic and nonvolcanic seamounts, and the Southern Tyrrhenian with the volcanic arc along the Sicilian‐Calabrian margin. The Northern Tyrrhenian basin system of normal faults trends roughly N‐S to turn NW‐SE to the east [ Mauffret and Contruccci , ; Moeller et al ., ]. This basin is spotted by small‐scale magmatic intrusions [ Moeller et al ., ] that decrease in age eastward [ Bartole , ].…”
Section: Geodynamic and Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The extension of the Ligurian Basin stopped and shifted to the Tyrrhenian Sea while the Apennines-Calabrian subduction zone continued to roll back further southeast until late the Messinian, ~6 Ma (Faccenna et al, 2001;Advokaat et al, 2014). The opening rate was calculated with 7.8-10.3 mm/yr (Moeller et al, 2013). In the north, extension led to continental crustal thinning (Moeller et al, 2013), while 80 further south in the centre of the Tyrrhenian Basin, mantle was exhumed and serpentinised and intruded by Mid-Ocean-Ridge type (MOR-type and intraplate basalts) (Prada et al, 2016).…”
Section: Geological Structures and Geodynamics Of The Ligurian Sea Anmentioning
confidence: 99%
“…In continental lithosphere it has been observed that during rifting the upper crust is deformed by faulting while the lower crust generally supports ductile deformation (e.g., Odera et al, 2001;Moeller et al, 2013).The transition from brittle to ductile deformation depends on the temperature structure and the rock type. Earthquakes are generally restricted to domains of brittle deformation.…”
Section: Rheology Of Crust and Mantlementioning
confidence: 99%